Antioxidant activity and ROS-dependent apoptotic effect of scurrula ferruginea (jack) danser methanol extract in human breast cancer cell MDA-MB-231 - Marvibaigi, M. (Public Library of Science, 2016)
Scurrula ferruginea (Jack) Danser is one of the mistletoe species belonging to Loranthaceae family, which grows on the branches of many deciduous trees in tropical countries. This study evaluated the antioxidant activities of S. ferruginea extracts. The cytotoxic activity of the selected extracts, which showed potent antioxidant activities, and high phenolic and flavonoid contents, were investigated in human breast cancer cell line (MDA-MB-231) and non-cancer human skin fibroblast cells (HSF-1184). The activities and characteristics varied depending on the different parts of S. ferruginea, solvent polarity, and concentrations of extracts. The stem methanol extract showed the highest amount of both phenolic (273.51 \xB1 4.84 mg gallic acid/g extract) and flavonoid contents (163.41 \xB1 4.62 mg catechin/g extract) and strong DPPH\x95 radical scavenging (IC50 = 27.81 \xB5g/mL) and metal chelation activity (IC50 = 80.20 \xB5g/mL). The stem aqueous extract showed the highest ABTS\x95+ scavenging ability. The stem methanol and aqueous extracts exhibited dose-dependent cytotoxic activity against MDA-MB-231 cells with IC50 of 19.27 and 50.35 \xB5g/mL, respectively. Furthermore, the extracts inhibited the migration and colony formation of MDA-MB-231 cells in a concentration-dependent manner. Morphological observations revealed hallmark properties of apoptosis in treated cells. The methanol extract induced an increase in ROS generation and mitochondrial depolarization in MDA-MB-231 cells, suggesting its potent apoptotic activity. The present study demonstrated that the S. ferruginea methanol extract mediated MDA-MB-231 cell growth inhibition via induction of apoptosis which was confirmed by Western blot analysis. It may be a potential anticancer agent, however, its in vivo anticancer activity needs to be investigated. \xA9 2016 Marvibaigi et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.